118k views
4 votes
Plz help me with this

Plz help me with this-example-1
User Daviid
by
5.7k points

2 Answers

5 votes

Answer:


(1)/(y^(3) )

Explanation:

Using the rule of exponents


(a^(m) )/(a^(n) )
(1)/(a^((n-m)) ) → n > m

Hence


(y^(-5) )/(y^(-2) ) =
(1)/(y^((-2-(-5))) ) =
(1)/(y^(3) )

User Don Bright
by
6.0k points
3 votes

Answer:
\bold{(1)/(y^3)}

Explanation:


(y^(-5))/(y^(-2))\quad =(y^(-5+5))/(y^(-2+5))\quad =(y^0)/(y^3)\quad =\large\boxed{(1)/(y^3)}

User Johannes Egger
by
6.5k points